Upper and lower solutions method for higher order fractional initial value problems. Issue 1 (2nd January 2017) - Guezane-Lakoud, Assia; Khaldi, Rabah
ABSTRACT: This paper concerns the existence of solution to an initial fractional problem of arbitrary order. The main tools for this study are the lower ad upper solutions method and Schauder's fixed point Theorem.